Understanding the reading practices of first-year university students through their experiences - Madoda Cekiso; Naomi Boakye; Florence Olifant (Literator)
Many studies have been conducted on the important role played by English reading literacy in the South African context and in many higher education institutions around the world. These studies come to the consensus that reading is considered the most important academic skill in any academic context, especially in institutions of higher education. However, because of a range of factors, many students lack the required level of reading proficiency. One important dimension of reading development often overlooked in research is the reading practices that students engage in. The current study, therefore, examines university students’ reading practices in the language of instruction, as well as the factors underlying these practices. The study was qualitative in nature and a case study design was followed. A questionnaire with open-ended questions was used to collect data from 65 respondents purposively selected. Content analysis was used to analyse students’ responses regarding their reading practices in English. The results showed that students did not read widely or extensively. They only read the books that were required of them to do better on assignments and tests. Additionally, the students’ reading preferences were influenced by the accessibility of social media and websites on the Internet. Students reported reading more posts on social media and websites than printed books.